Research of crack detection and delay crack propagation on a nonlinear rotor - Liu, Jun (Strojniški vestnik, 2018)
The existence and propagation of a crack on an engine's nonlinear rotor can easily cause a serious accident, so it is quite essential to detect a crack in the rotor system through analysis of the rotor's vibration signals and to delay the crack propagation. The vibration signals of the cracked rotor show the non-periodic and the nonlinearity within a transient response. The fault characteristics of the crack can be easily hidden in other vibrational components and are difficult to extract from transient signals. In the paper, the Hilbert-Huang marginal spectrum (HHMS) method is proposed to realize the extraction of crack's fault characteristics in a nonlinear rotor system. In addition, the crack's opening and closing degrees at any rotating position are also put forward representing the crack propagation, and some tactics of the delaying crack propagation are proposed based on the effect on the crack's opening and closing degree caused by the change of different rotor parameters. The simulation results show that the HHMS method can detect a crack early at about five per cent of the depth of the rotor's diameter, and the methods of delaying crack propagation can effectively delay propagation. Experimental results verify the effectiveness of the proposed HHMS method.
Keywords: crack detection; cracked rotors; delaying crack propagation; Hilbert-Huang marginal spectrum; Hilbert-Huangov marginalni spekter; odkrivanje razpok; prehodni odgovor; razpokani rotorji; transient response; upočasnitev napredovanja razpok; valjčna metoda